2018
DOI: 10.1016/s2215-0366(18)30268-2
|View full text |Cite|
|
Sign up to set email alerts
|

The relationship between cortical glutamate and striatal dopamine in first-episode psychosis: a cross-sectional multimodal PET and magnetic resonance spectroscopy imaging study

Abstract: SummaryBackgroundThe pathophysiology of psychosis is incompletely understood. Disruption in cortical glutamatergic signalling causing aberrant striatal dopamine synthesis capacity is a proposed model for psychosis, but has not been tested in vivo. We therefore aimed to test the relationship between cortical glutamate concentrations and striatal dopamine synthesis capacity, and psychotic symptoms.MethodsIn this cross-sectional multimodal imaging study, 28 individuals with first-episode psychosis and 28 healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
64
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 101 publications
(76 citation statements)
references
References 31 publications
9
64
2
1
Order By: Relevance
“…This is in keeping with the imaging studies discussed above, in which both increased dopamine and glutamate measures were observed in the striatum in schizophrenia, which could potentially result from increased activity of glutamatergic projection to the striatum. Other studies found the same relationship between cortical glutamate and striatal dopamine in clinical high‐risk and first‐episode psychosis patients, but not in controls.…”
Section: Factors Underlying Glutamatergic and Dopaminergic Dysfunctionmentioning
confidence: 74%
“…This is in keeping with the imaging studies discussed above, in which both increased dopamine and glutamate measures were observed in the striatum in schizophrenia, which could potentially result from increased activity of glutamatergic projection to the striatum. Other studies found the same relationship between cortical glutamate and striatal dopamine in clinical high‐risk and first‐episode psychosis patients, but not in controls.…”
Section: Factors Underlying Glutamatergic and Dopaminergic Dysfunctionmentioning
confidence: 74%
“…Because CB1R binding inhibits calcium entry into the presynaptic neuron via N-, P-, and Q-type calcium channels, 58 , 59 the presence of fewer CB1Rs may dysregulate calcium and potassium channels, leading to neurochemical alterations in psychosis. 34 , 35 , 36 , 60 , 61 Because CB1Rs modulate neurotransmitters implicated in psychosis, including dopamine, 62 glutamate, 63 and γ-aminobutyric acid, 58 future studies are needed to investigate whether CB1R alterations precipitate other neurochemical alterations in psychosis.…”
Section: Discussionmentioning
confidence: 99%
“…Another strategy could be to use biomarkers to identify patients who may have TRS to either exclude them or enrich samples for studies of TRS. There is evidence that imaging measures, such as for dopamine, glutamate and resting-state connectivity may be useful for this [74][75][76][77]. A general issue we identified in many studies is limited sample characterisation (e.g.…”
Section: Strengths and Limitationsmentioning
confidence: 99%